Mediating medical negligence claims in Malaysia: an option for reform? - Jahn Kassim, Puteri Nemie (LexisNexis, 2008)
The present tort system has been criticised as not being a suitable mechanism for compensating victims of medical negligence. The deficiencies of the system has been identified and proven as not being able to fulfill objectives such as providing fair and adequate compensation, maintaining equity between injured victims with similar needs, providing deterrence and incentives to accident reduction. Alternatives to the tort system have been advocated, particularly in employing various methods of alternative dispute resolution to reach a settlement between disputing parties. Such methods can be seen to do away with the rigours of litigation by offering settlement through a fairer, cheaper and more helpful approach. Compared to other methods of alternative dispute resolution, mediation seems to offer a costless process of integrative bargaining. It does not emphasize on who should win or lose, who is right or wrong. Rather, it focuses on goals of reconciliation and personal transformation. In mediation, parties participate directly in what is thought to be an informal and voluntary dispute resolution process that may offer a novel and promising approach in resolving claims. In handling medical negligence claims, mediation can be seen as the main form of dispute resolution, which provides speedy, economical and trauma-free alternative to litigation. Experiences from countries that have employed mediation for medical negligence disputes such as England and Australia can offer valuable lessons to Malaysia in assessing whether this alternative can be a viable option in solving the problems inherent in medical negligence litigation in Malaysia.